Use cofunction of the given trigonometric function,

\(\displaystyle{\sec{{x}}}={\cos{{e}}}{c}{\left({90}^{\circ}−{x}\right)}\)

Given,

\(\displaystyle{{\sec{{6.7}}}^{\circ}}\)

Here \(\displaystyle{x}={6.7}^{\circ}\)

\(\displaystyle{{\sec{{6.7}}}^{\circ}=}{\cos{{e}}}{c}{\left({90}^{\circ}−{6.7}^{\circ}\right)}\)

\(\displaystyle={\cos{{e}}}{c}{\left({83.3}^{\circ}\right)}\)

\(\displaystyle={1.006876}\)

\(\displaystyle\approx{1.0069}\)

Therefore \(\displaystyle{{\sec{{6.7}}}^{\circ}=}{1.0069}\)

Now use cofunction of the given trigonometric function,

\(\displaystyle{\cos{{e}}}{c}{x}={\sec{{\left({90}^{\circ}−{x}\right)}}}\)

Given,

\(\displaystyle{\cos{{e}}}{c}{\left({83.3}^{\circ}\right)}\)

Here \(\displaystyle{x}={83.3}^{\circ}\)

\(\displaystyle{\cos{{e}}}{c}{83.3}^{\circ}={\sec{{\left({90}^{\circ}−{83.3}^{\circ}\right)}}}\)

\(\displaystyle={{\sec{{6.7}}}^{\circ}}\)

\(\displaystyle={1.006876}\)

\(\displaystyle\approx{1.0069}\)

Therefore, \(\displaystyle{\cos{{e}}}{c}{83.3}^{\circ}={1.0069}\)

We clearly see that trigonometric functions are cofunction of one another.

Sum of the angles of two cofunctions is \(\displaystyle{90}^{\circ}\) that is the angles are complementary angles.

Therefore the pair of a trigonometric function is,

\(\displaystyle{\left({{\sec{{6.7}}}^{\circ},}{\cos{{e}}}{c}{83.3}^{\circ}\right)}={\left({1.0069},{1.0069}\right)}\)

\(\displaystyle{\sec{{x}}}={\cos{{e}}}{c}{\left({90}^{\circ}−{x}\right)}\)

Given,

\(\displaystyle{{\sec{{6.7}}}^{\circ}}\)

Here \(\displaystyle{x}={6.7}^{\circ}\)

\(\displaystyle{{\sec{{6.7}}}^{\circ}=}{\cos{{e}}}{c}{\left({90}^{\circ}−{6.7}^{\circ}\right)}\)

\(\displaystyle={\cos{{e}}}{c}{\left({83.3}^{\circ}\right)}\)

\(\displaystyle={1.006876}\)

\(\displaystyle\approx{1.0069}\)

Therefore \(\displaystyle{{\sec{{6.7}}}^{\circ}=}{1.0069}\)

Now use cofunction of the given trigonometric function,

\(\displaystyle{\cos{{e}}}{c}{x}={\sec{{\left({90}^{\circ}−{x}\right)}}}\)

Given,

\(\displaystyle{\cos{{e}}}{c}{\left({83.3}^{\circ}\right)}\)

Here \(\displaystyle{x}={83.3}^{\circ}\)

\(\displaystyle{\cos{{e}}}{c}{83.3}^{\circ}={\sec{{\left({90}^{\circ}−{83.3}^{\circ}\right)}}}\)

\(\displaystyle={{\sec{{6.7}}}^{\circ}}\)

\(\displaystyle={1.006876}\)

\(\displaystyle\approx{1.0069}\)

Therefore, \(\displaystyle{\cos{{e}}}{c}{83.3}^{\circ}={1.0069}\)

We clearly see that trigonometric functions are cofunction of one another.

Sum of the angles of two cofunctions is \(\displaystyle{90}^{\circ}\) that is the angles are complementary angles.

Therefore the pair of a trigonometric function is,

\(\displaystyle{\left({{\sec{{6.7}}}^{\circ},}{\cos{{e}}}{c}{83.3}^{\circ}\right)}={\left({1.0069},{1.0069}\right)}\)